Defining the Role of Pannexin1 in Skeletal Muscle and Satellite Cell Function in vivo and ex vivo Using a Novel Conditional Knockout Mouse Model - Beaudry, Kathryn (Université d'Ottawa / University of Ottawa, 2024)
It has been previously shown that pannexin 1 (Panx1) channels, well known for their role in ATP release, play a key role in myogenesis. However, its role in muscle development remains to be elucidated. Using a novel skeletal-muscle-specific Panx1 knockout (Panx1^smKO) mouse model, this thesis highlights the influences Panx1 plays in muscular development and maintenance, as well as in muscle function. Loss of Panx1 led to a fiber-type switch coinciding with smaller fibers in both the tibialis anterior (TA) and soleus (SOL) muscles, reduced strength, and increased fatigue resistibility in adult male mice. Notably, these mice were observed to have fewer quiescent satellite cells (SCs) with a reduction in commitment to the myogenic lineage and a decline in fusion capabilities. Additionally, Panx1 was found to be preferentially localized among fiber-types leading to smaller type I fibers in the SOL of male mice, which is likely linked to fewer SCs in this muscle at juvenile age. On the other hand, the reduction in fiber size found in the TA due to loss of Panx1 was instead due to a switch in fiber type composition. In adult mice, both muscles Panx1^smKO had less quiescent SCs. In terms of muscle function, we found that loss of Panx1 led to reduced muscle strength, but increased resistance in male mice. Notably, all the effects resulting from loss of Panx1 in the skeletal muscle identified here in male mice were non-significant in females. Collectively, these results indicate that Panx1 plays sex-specific and muscle-specific roles in skeletal muscle development, maintenance of normal fiber type composition and quiescent SC pool, as well as in muscle function.
Keywords: Pannexin; Skeletal muscle; Development; Stem cell